Perbandingan Daya Tahan Kardiorespirasi antara Perokok Aktif dan Perokok Pasif Pemain Futsal Forza Lubuklinggau - Iswahyudi, Eka; Suhdy, Muhammad; Supriyadi, Muhammad (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2024)
This study aims to determine the comparison of kerdiorespiration endurance between active smokers and passive smokers futsal player Forza Lubuklinggau. This type of research is quantitative with non-experimental research methods and comparative research designs. In this study intends to provide an overview of information whether there is a comparison of cardiorespiratory endurance between active smokers and passive smokers futsal player Forza Lubuklinggau. The population of all players is 35 players and the purposive sampling technique is 24 players, consisting of 12 active smokers and 12 passive smokers. Data collection techniques use surveys, tests, and measurements. Data analysis techniques use normality tests, homogeneity tests, and hypothesis tests. The results showed that active smokers had an average cardiorespiratory endurance of 33.9250. Passive smoking had an average cardiorespiratory endurance of 43,4420. Based on the results of the difference between active smokers and passive smokers, a significance value of 0.00 is obtained smaller than 0.05 (p < 0.05). Because the value (p < 0.05), and t count (5,941) is greater than t table (2.074), it can be concluded that the respiratory endurance of active smokers is very low, while the cardiorespiratory endurance of passive smokers is good, and there is a significant difference between the two, where the cardiorespiratory endurance of passive smokers exercises better than active smokers in futsal players Forza Lubuklinggau. Keywords: Endurance, Active Passive Smokers